Curcumin facilitates a transitory cellular stress response in Trembler-J mice - Okamoto, Yuji (Oxford University Press, 2013)
We have previously shown that oral administration of curcumin significantly decreases the percentage of apoptotic Schwann cells and partially mitigates the severe neuropathy phenotype of the Trembler-J (Tr-J) mouse model in a dose-dependent manner. Here we compared the gene expression in sciatic nerves of 2-week-old pups and adult Tr-J with the same age groups of wild-type mice and found a significant increase in gene expression for hypoxia, inflammatory response and heat-shock proteins, the latter specifically the Hsp70 family, in Tr-J mice. We also detected an activation of different branches of unfolded protein responses (UPRs) in Tr-J mice. Administering curcumin results in lower expression of UPR markers suggesting it relieves endoplasmic reticulum (ER) cell stress sensors in sciatic nerves of Tr-J mice while the level of heat-shock proteins stays comparable to untreated Tr-J mice. We further tested if Hsp70 levels could influence the severity of the Tr-J neuropathy. Notably, reduced dosage of the Hsp70 strongly potentiates the severity of the Tr-J neuropathy, though the absence of Hsp70 had little effect in wild-type mice. In aggregate, these data provide further insights into the pathological disease mechanisms caused by myelin gene mutations and further support the exploration of curcumin as a therapeutic approach for selected forms of inherited neuropathy and potentially for other genetic diseases due to ER-retained mutants.